(3eNJUQ aj CUhd Yde GdbGajIs - (3CHh GdHQcGJ YHO GdQMef Hf CHj SYjO GdGfHGQj GdfMhjs
(3ChdgG (B:s
(3hHYO aEfi ChOYJ ai gPG GdeNJUQ ef CUhd Yde GdbGajI hbSeJg aUhdkG djchf COfi Zdi eJdbfg hUhdkG s
(3BNQgG (B:s
(3aPgH HYVge Edi Cfg djS HYjH hGdPi Ydjg GdLeghQ hGdePgH GdeTghQ Gfg YjH hGddg CYde Je GdehLR ai Yde GdbhGai HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs